Association of single nucleotide polymorphisms in the NRF2 promoter with vascular stiffness with aging - Shimizu, Sunao; Mimura, Junsei; Hasegawa, Takanori; Shimizu, Eigo; Imoto, Seiya; Tsushima, Michiko; Kasai, Shuya; Yamazaki, Hiromi; Ushida, Yusuke; Suganuma, Hiroyuki; Tomita, Hirofumi; Yamamoto, Masayuki; et al. (PloS one, 2020)
Pulse wave velocity (PWV), an indicator of vascular stiffness, increases with age and is increasingly recognized as an independent risk factor for cardiovascular disease (CVD). Although many mechanical and chemical factors underlie the stiffness of the elastic artery, genetic risk factors related to age-dependent increases in PWV in apparently healthy people are largely unknown. The transcription factor nuclear factor E2 (NF-E2)-related factor 2 (Nrf2), which is activated by unidirectional vascular pulsatile shear stress or oxidative stress, regulates vascular redox homeostasis. Previous reports have shown that a SNP in the NRF2 gene regulatory region (-617C>A; hereafter called SNP-617) affects NRF2 gene expression such that the minor A allele confers lower gene expression compared to the C allele, and it is associated with various diseases, including CVD. We aimed to investigate whether SNP-617 affects vascular stiffness with aging in apparently healthy people. Analyzing wide-ranging data obtained from a public health survey performed in Japan, we evaluated whether SNP-617 affected brachial-ankle PWV (baPWV) in never-smoking healthy subjects (n = 642). We also evaluated the effects of SNP-617 on other cardiovascular and blood test measurements. We have shown that not only AA carriers (n = 55) but also CA carriers (n = 247) show arterial stiffness compared to CC carriers (n = 340). Furthermore, SNP-617 also affected blood pressure indexes such as systolic blood pressure and mean arterial pressure but not the ankle brachial pressure index, an indicator of atherosclerosis. Multivariate analysis showed that SNP-617 accelerates the incremental ratio of baPWV with age. This study is the first to show that SNP-617 affects the age-dependent increase in vascular stiffness. Our results indicate that low NRF2 activity induces premature vascular aging and could be targeted for the prevention of cardiovascular diseases associated with aging.